Aging behavior of Ni-Mn-Ga/silicone particulate composites exhibiting large recoverable magnetostrain. (1st April 2023) - Chiu, Wan-Ting; Sratong-on, Pimpet; Tahara, Masaki; Chernenko, Volodymyr; Hosoda, Hideki
Abstract: Single crystalline Ni-Mn-Ga particles/silicone composites are new ferromagnetic shape memory materials, exhibiting a large reversible magnetic field induced strain (MFIS), are greatly demanded for actuators and sensors toward future technologies. In the present work, we studied a long-term aging effect on the mechanical and recoverable MFIS properties of the Ni-Mn-Ga/silicone particulate composites containing different amounts of filler. It was shown that despite a strong decline of the effective stiffness of pure silicone during long aging, the stiffness reduction of composites was much less pronounced and barely affected the characteristics of the large recoverable MFIS. Graphical abstract: Image, graphical abstract